Women, Humanists and Transcendents in Abidah El Khalieqy's Novels - Abid Sahulata Lingga Sakti; Anwar Effendi (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2024)
Differences between men and women always give rise to differences and social status, including gender inequality. Women are still placed and considered lower than men and tend to have a lower status. Based on prophetic feminism, women's role is domestic because women still have beneficial values ​​even if they are at home. The aim of this research is to describe the value of prophetic feminism in the novel Mataraisa by Abidah el khalieqy. The method used in this research is descriptive qualitative. Data collection is carried out with documentation. The analysis carried out is by carefully reading several novels and then concluding with expert opinions. The novel Mataraisa by Abidah el Khalieqy as a whole illustrates that the role of female characters is very close to the prophetic values ​​of feminism which are based on moral and religious values. All women's roles are described regularly in religious values, so that it does not harm women in carrying out activities in the public and domestic spheres.